Analisis Perubahan Kebijakan Pajak di Negara GCC dalam Perspektif Ekonomi Islam - Rachmania Nurul Fitri Amijaya; Mohammad Yusron Sholikhin (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
G.C.C. countries use oil as a significant source of state revenue because the G.C.C. region is a collection of world oil-producing countries. However, since the world oil price slumped from 2005-2008, governments have changed course by imposing taxes on their citizens. The point of this study is to argue the G.C.C. countries that have changed their tax-free system in their economy into countries that apply taxes today. Then, the views of some Muslim scientists related to taxation are related to changes in tax policy in G.C.C. countries. The qualitative method is used in this paper with a critical approach and analysis of several kinds of literature and financial reports relating to changes in tax policy in the G.C.C. area. The results of this study explain that the G.C.C. countries compile a value-added tax of 5%, which is applied to several basic needs such as food, clothing, water, and electricity bills. Later, some Muslim scientists agreed on the existence of taxes for the common good, a source of revenue for public facilities and services.